2020
DOI: 10.3389/fimmu.2020.563362
|View full text |Cite
|
Sign up to set email alerts
|

New Immunoinformatics Tools for Swine: Designing Epitope-Driven Vaccines, Predicting Vaccine Efficacy, and Making Vaccines on Demand

Abstract: Novel computational tools for swine vaccine development can expand the range of immunization approaches available to prevent economically devastating swine diseases and spillover events between pigs and humans. PigMatrix and EpiCC are two new tools for swine T cell epitope identification and vaccine efficacy analysis that have been integrated into an existing computational vaccine design platform named iVAX. The iVAX platform is already in use for the development of human vaccines, thus integration of these to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 77 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…This vaccine, which is increasingly used in Spanish pig farms, consists of porcine RVA strains Gottfried (G4P6), OSU (G5P7) and A2 (G9P7) which have been modified a long time ago [12]. Moise et al [59] used computational tools to analyze the potential efficacy of this vaccine and demonstrated that T cell epitope cross-conservation between the vaccine and RVA porcine strains circulating in the United States is genotype-specific and limited to homologous strains. However, more than 200,000 sows are vaccinated every year in Spain with this vaccine (personal communication of R. Menjon) and no pharmacovigilance events suggesting a possible lack of efficacy have been reported to the Spanish Agency of Medicines and Medical Devices (available at https:// www.aemps.gob.es/acciones-informativas-medicamentos-veterinarios/?cat=291, accessed on 18 January 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This vaccine, which is increasingly used in Spanish pig farms, consists of porcine RVA strains Gottfried (G4P6), OSU (G5P7) and A2 (G9P7) which have been modified a long time ago [12]. Moise et al [59] used computational tools to analyze the potential efficacy of this vaccine and demonstrated that T cell epitope cross-conservation between the vaccine and RVA porcine strains circulating in the United States is genotype-specific and limited to homologous strains. However, more than 200,000 sows are vaccinated every year in Spain with this vaccine (personal communication of R. Menjon) and no pharmacovigilance events suggesting a possible lack of efficacy have been reported to the Spanish Agency of Medicines and Medical Devices (available at https:// www.aemps.gob.es/acciones-informativas-medicamentos-veterinarios/?cat=291, accessed on 18 January 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the concerns that we had when performing the in silico predictions based on a single prediction tool, we decided to perform a multiparametric analysis not only based on NetMHCpan. Despite novel immunoinformatics tools have been recently developed [ 58 ], at the time of the analysis little data was available from swine [ 59 , 60 , 61 , 62 ], which forced to complete our multiparametric prediction tool with experimental data obtained mainly from human and mouse studies. Most probably due to the imperfections of our predictive methodology, our approach has allowed the identification of only one promiscuously recognized ASFV T-cell determinant within the Georgia2007/1 MGF100-1L protein.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, highly conserved cytotoxic T-cell epitopes have been identified in ASFV encoded proteins through a computational vaccine design platform named iVAX [113,114]. A Tcell-directed ASF DNA vaccine containing the predicted swine MHC class I and class II epitopes was then developed, and the immunogenicity of this novel vaccine is being assessed [115][116][117]. Given the potential risk of integration into the host genome associated with DNA vaccines, the mRNA-based vaccine approach has the potential to lead to improvements for safe and effective ASF vaccines for marketing.…”
Section: T-cell-directed Mrna Vaccine For Asfvmentioning
confidence: 99%